Agency within a socially regulated labour market: A study of ‘unorganised’ agricultural labour in Kerala - Terah Sportel (Geoforum, 2013)
This paper combines insights from the social structures of accumulation framework, and a carefully delineated understanding of agency, to provide a conceptual and empirical contribution to the field of labour geography. This framework allows for a nuanced understanding of the complexity of the labour process as evinced by in-depth research conducted on the coconut industry in Kerala, India. The Kerala coconut industry has experienced various market changes post-agricultural liberalisation in the mid- 1990s. The Government of Kerala has indicated these changes, including increasing imports of palm oil and new trade agreements, have led to a crisis; an issue of considerable importance to the state economy and farmers’ livelihoods. More recent government explanations for the crisis include a labour shortage; particularly an inadequate supply of coconut harvesters. This simplistic explanation (based on neoclassi- cal economic models) masks the complexity of locally constituted labour dynamics in an ‘unorganised’ labour market. A more nuanced understanding reveals that labour market organisation varies by place and difficulties are more adequately explained through changing agrarian relations and the inability to sufficiently control labour. These findings lead to three primary arguments: (1) labour markets are socially and spatially structured and their regulation varies with geographical, historical and political– economic processes in particular places; (2) unorganised labour is able to regulate itself socially and informally, albeit in small ways; and (3) a structural approach is valuable to understand labour agency and the ways informal, unorganised labour is regulated.